2004
DOI: 10.1093/ptj/84.6.524
|View full text |Cite
|
Sign up to set email alerts
|

Physiologic Evidence for the Efficacy of Positive Expiratory Pressure as an Airway Clearance Technique in Patients With Cystic Fibrosis

Abstract: Background and Purpose. Individuals with cystic fibrosis (CF) have large amounts of infected mucus in their lungs, which causes irreversible lung tissue damage. Although patient-administered positive expiratory pressure (PEP) breathing has been promoted as an effective therapeutic modality for removing mucus and improving ventilation distribution in these patients, the effects of PEP on ventilation distribution and gas mixing have not been documented. Therefore, this preliminary investigation described respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 24 publications
1
29
0
2
Order By: Relevance
“…They have shown in surgical patients that periodic continuous positive airway pressure by mask was superior to standard postoperative conventional therapy in decreasing atelectasis and improving gas exchange (87). The use of positive end-expiratory pressure maneuvers in patients with cystic fibrosis has been shown to increase lung volumes and promote peripheral collateral air movement distal to bronchi obstructed with mucus (88). Taken together, a reasonable conclusion is that chest physical therapy that includes maneuvers that increase lung volume works because enhanced collateral ventilation at higher lung volumes allows air to accumulate distal to airways narrowed or obstructed by inflammation and secretions, and that, during coughing and expiration, the resultant higher lung volumes and increased air pressure in alveoli distal to the airways obstruction promotes mucus movement to the more proximal, larger airways (89).…”
Section: Physical Therapymentioning
confidence: 99%
“…They have shown in surgical patients that periodic continuous positive airway pressure by mask was superior to standard postoperative conventional therapy in decreasing atelectasis and improving gas exchange (87). The use of positive end-expiratory pressure maneuvers in patients with cystic fibrosis has been shown to increase lung volumes and promote peripheral collateral air movement distal to bronchi obstructed with mucus (88). Taken together, a reasonable conclusion is that chest physical therapy that includes maneuvers that increase lung volume works because enhanced collateral ventilation at higher lung volumes allows air to accumulate distal to airways narrowed or obstructed by inflammation and secretions, and that, during coughing and expiration, the resultant higher lung volumes and increased air pressure in alveoli distal to the airways obstruction promotes mucus movement to the more proximal, larger airways (89).…”
Section: Physical Therapymentioning
confidence: 99%
“…to temporarily increase FRC and VT in combination with techniques to mobilize and evacuate secretions, Fig. 3 [5,6,14,19,21,59]. The latter is performed by the forced expiration technique (FET), huffing and/or coughing while the expiratory resistor is temporarily put aside [1,2,60e63].…”
Section: H E a L T H Y O B S T R U C T I V E Hyperinflated Chest S Cmentioning
confidence: 99%
“…The latter is performed by the forced expiration technique (FET), huffing and/or coughing while the expiratory resistor is temporarily put aside [1,2,60e63]. PEP with FET has been shown to be an effective airway clearance technique [5,6,14,64,65] and better maintenance of lung function over time and improved physical function in patients with cystic fibrosis [6,22,66,67]. Several studies have reported its effect to be equal to other airway clearance techniques such as positioning and postural drainage [5,59,64,68e77] or superior to chest wall oscillation, postural draining with percussions and OscPEP [22,66,67].…”
Section: H E a L T H Y O B S T R U C T I V E Hyperinflated Chest S Cmentioning
confidence: 99%
See 2 more Smart Citations